Temperature of photoanode for photoelectrochemical water oxidation. (May 2023) - Biswas, Neeraj Kumar; Srivastav, Anupam; Saxena, Sakshi; Verma, Anuradha; Dutta, Runjhun; Srivastava, Manju; Upadhyay, Sumant; Satsangi, Vibha Rani; Shrivastav, Rohit; Dass, Sahab
Abstract: Solar-light-driven photoelectrochemical that can utilise water for high-performance artificial photosynthesis for low-cost green hydrogen fuel production. However, the interaction of photoanode with water is crucial to its heterogeneous water oxidation for sustainable fuel production for the replacement of fossil fuels. Here, we report experiment investigations of photoelectrode with temperature for solar energy conversion. These measurements revealed that a rise in temperature affects the catalytic generation of hydrogen in three routes, viz., minimising the required energy for water splitting, reducing bandgap energy and mitigating the resistance at the interface. Graphical abstract: Image 1 Highlights: The bandgap of PCNDTO reduces with the increase in electrolytic temperature. Resistance at semiconductor/electrolytes interface with rising temperature of electrolytes. Faradaic efficiency of 92.49% for hydrogen production achieved at 45 °C in aqueous solution of NaOH + F6 NaP.